Pertanian Berbasis Green Economy: Langkah Nyata Menuju Masa Depan Ramah Lingkungan - Rizki Febri Eka Pradani; Nurul Kamalia (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
The implementation of green economy principles in duck farming aims to enhance sustainable productivity, minimize environmental degradation, and improve the economic well-being of rural communities. This study seeks to explore how sustainable agricultural practices are applied through a green economy approach at the community level. Employing a qualitative method, the research investigates the social context, meanings, and community interpretations of environmentally friendly farming systems. The findings reveal that the transition toward sustainable agriculture can be achieved through community-based initiatives, local innovations, and the use of organic resources. Efforts led by Mudzakkir and the Aspekpro farming community demonstrate that agricultural productivity does not necessarily rely on chemical fertilizers. Instead, the production of organic fertilizer from agricultural waste and livestock manure has significantly improved soil health and crop yields. Nevertheless, several challenges persist, including limited access to technical knowledge, the absence of mid-scale production equipment, and a lack of policy support for organic fertilizer development. On the positive side, environmental awareness, strong community leadership, and a culture of mutual cooperation serve as essential driving forces that reinforce the green economy approach. This study contributes to the broader discourse on sustainable agricultural development by offering a practical illustration of how grassroots participation can foster ecologically sound and socially inclusive farming systems